2003
DOI: 10.1152/ajpendo.00552.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic effects of maternal alcohol intake and adrenalectomy on left ventricular hypertrophy in rat offspring

Abstract: In humans, low birth weight and increased placental weight can be associated with cardiovascular disease in adulthood. Low birth weight and increased placental size are known to occur after fetal alcohol exposure or prenatal glucocorticoid administration. Thus the effects of removing the alcohol-induced increase in maternal corticosterone by maternal adrenalectomy on predictors of cardiovascular disease in adulthood were examined in rats. Alcohol exposure of dams during the last 2 wk of gestation resulted in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 72 publications
(71 reference statements)
9
31
1
1
Order By: Relevance
“…It may be hypothesised that female offspring are more protected from in utero insults by the relative ease with which the placenta adapts in the face of adverse conditions. The relative malleability of the female placenta is also observed in other species, including the rat, where ethanol exposure in utero leads to decreased 11b-hydroxysteroid dehydrogenase-2 activity in female offspring (Wilcoxon et al 2003), and in human studies, where placental up-regulation of 11b-hydroxysteroid dehydrogenase-2 activity in response to antenatal steroid administration occurs specifically in female offspring (Stark et al 2009). 11b-Hydroxysteroid dehydrogenase-2 is associated with improved physiological stability, particularly in infants born preterm, and it is therefore unsurprising to note that levels are decreased by a physiological insult such as alcohol consumption and increased by antenatal steroid administration (which confers advantage in neonatal outcome; Stark et al 2009).…”
Section: Humanmentioning
confidence: 76%
See 3 more Smart Citations
“…It may be hypothesised that female offspring are more protected from in utero insults by the relative ease with which the placenta adapts in the face of adverse conditions. The relative malleability of the female placenta is also observed in other species, including the rat, where ethanol exposure in utero leads to decreased 11b-hydroxysteroid dehydrogenase-2 activity in female offspring (Wilcoxon et al 2003), and in human studies, where placental up-regulation of 11b-hydroxysteroid dehydrogenase-2 activity in response to antenatal steroid administration occurs specifically in female offspring (Stark et al 2009). 11b-Hydroxysteroid dehydrogenase-2 is associated with improved physiological stability, particularly in infants born preterm, and it is therefore unsurprising to note that levels are decreased by a physiological insult such as alcohol consumption and increased by antenatal steroid administration (which confers advantage in neonatal outcome; Stark et al 2009).…”
Section: Humanmentioning
confidence: 76%
“…Animal models Male-specific outcomes Langley-Evans et al (1996) Low-protein diet gives elevated blood pressure in male offspring relative to females Rat Kwong et al (2000) Low-protein diet increases blood pressure in male offspring Rat Ozaki et al (2001) Nutrient restriction (30% reduction) increases blood pressure and vascular dysfunction more in male offspring Rat Dodic et al (2002) Dexamethasone exposure gives increased blood pressure more in male offspring Sheep Franco Mdo et al (2002) Nutrient restriction (50%) reduces eNOS expression in aorta of male offspring Rat Alexander (2003) Reduced uterine perfusion causes sustained increase in blood pressure in male offspring Rat Ortiz et al (2003) Antenatal dexamethasone injection persistently elevates blood pressure in male offspring Rat Hemmings et al (2005) Hypoxia Lee & Rivier (1996) Ethanol exposure leads to exaggerated HPA stress response in young female offspring Rat Khan et al (2003) High-fat diet increases blood pressure in female offspring Rat Wilcoxon et al (2003) Ethanol exposure leads to decreased placental 11b-hydroxysteroid dehydrogenase-2 levels and left ventricular hypertrophy in female offspring High-fat diet leads to DNA hypomethylation in female placenta only Mouse Rodriguez et al (2011) Betamethasone exposure reduces associative learning more in female offspring Baboon Vickers et al (2011) Fructose exposure gives decreased placental weight, increased plasma leptin and glucose in female offspring Rat Epidemiology Male-specific outcomes Zaren et al (2000) Maternal smoking decreases birth weight and head circumference proportionally more in male offspring Human Goldenberg et al (2006) Placentas from preterm deliveries showed more lymphohistiocytic infiltration in male offspring Human Haley et al (2006) Prenatal exposure to alcohol increases the heart rate of female infant offspring more than males, but with the males showing a greater increase in plasma cortisol Human Mingrone et al (2008) Male offspring of obese mothers have higher levels of insulin secretion in response to GTT Human Female-specific outcomes Roseboom et al (2001) Higher rates of obesity in female offspring conceived during famine Human Clifton (2005) Maternal asthma in pregnancy causes altered placental glucocorticoid metabolism and growth in female offspring Human Stark et al (2009) Antenatal betamethasone administration increased placental 11b-hydroxysteroid dehydrogenase-2 activity in female offspring and this was positively correlated with mean arterial blood pressure…”
Section: Main Results Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that a high-fat diet provokes undermethylation only of female placentas in mice, which is indicative of an active response to this stressor (GallouKabani et al 2010); this was confirmed by another study showing that female placenta was more responsive to nutritional perturbations by more significant changes in the placental transcriptome (Mao et al 2010). In rats, this higher adaptation was also observed for the female placenta in contrast to its male counterpart in response to ethanol by decreasing the 11β-hydroxysteroid dehydrogenase-2 activity (Wilcoxon et al 2003). In addition, in humans, the female placenta responds to antenatal steroid administration by upregulating 11β-hydroxysteroid dehydrogenase-2 ).…”
Section: Sex Differences After Implantation: Another Source For Sex-smentioning
confidence: 80%